Grabados rupestres en La Mancha centro : documentacíon y estudio de un patrimonio desconocido = Rock engravings in La Mancha center : documentation and study of an unknown heritage - Rocío, Ramiro Rodero (Archaeopress Publishing Ltd, 2018)
This text deals with the documentation and interpretation of the rock sites located in La Mancha center (Spain), from the detailed study of the symbols that have been engraved in the rock.